2010
DOI: 10.1155/2011/378907
|View full text |Cite
|
Sign up to set email alerts
|

Neuron Regeneration and Proliferation Effects of Danshen and Tanshinone IIA

Abstract: This study evaluates the proliferative effects of danshen and its monomer extract, tanshinone IIA, on Schwann cell proliferation. A piece of silicone rubber was guided across a 15-mm gap in the sciatic nerve of a rat. This nerve gap was then filled with different concentrations of danshen (0–100 mg/mL). The results showed that danshen increased the expressions of uPA, cyclin D1, E and ERK, JNK, and P38 MAP kinases via the FGF-2 signaling pathway in a dose-dependent manner. RSC96, Schwann cells were also admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…In addition, elevating the proliferation ability of SCs is important for constructing tissue-engineered nerves (6). As a result, researchers have been exploring various promoting agents for SCs proliferation, such as interleukin-1β (14) and tanshinone IIA (15 Utilizing plant-derived traditional Chinese medicines to treat various types of diseases has a long history in East Asian countries, such as China, Korea and Japan (16). Furthermore, some western medicines are derived from major constituent of traditional Chinese medicine (17) Scutellaria baicalensis Georgi (Huangqin in Chinese), a traditional Chinese medicine, has been used to treat inflammation, fever, ulcers and cancer for hundreds of years (18)(19)(20) and a recent study has reported that flavonoids from the stems and leaves of S. baicalensis Georgi have neuroprotective effects (21).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, elevating the proliferation ability of SCs is important for constructing tissue-engineered nerves (6). As a result, researchers have been exploring various promoting agents for SCs proliferation, such as interleukin-1β (14) and tanshinone IIA (15 Utilizing plant-derived traditional Chinese medicines to treat various types of diseases has a long history in East Asian countries, such as China, Korea and Japan (16). Furthermore, some western medicines are derived from major constituent of traditional Chinese medicine (17) Scutellaria baicalensis Georgi (Huangqin in Chinese), a traditional Chinese medicine, has been used to treat inflammation, fever, ulcers and cancer for hundreds of years (18)(19)(20) and a recent study has reported that flavonoids from the stems and leaves of S. baicalensis Georgi have neuroprotective effects (21).…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al. (2011) reported that TSN IIA had a proliferative effect on neuronal cells; specifically, TSN IIA enhanced neuron regeneration [26]. Moreover, the neuroprotective effect of TSN IIA has also been reported in diabetic rats [27].…”
Section: Discussionmentioning
confidence: 99%
“…Many flavonoids or phytoestrogens, such as Tanshinone IIA, protect the heart against hypertrophy via the estrogen receptor [22,23]. However, there is no direct evidence showing that estrogen has the same protective effect.…”
Section: Introductionmentioning
confidence: 99%